PSYCHOMETRIC PROPERTIES OF SPIRITUAL INDEX OF WELL-BEING AMONG FILIPINO WOMEN WITH BREAST CANCER - Gil P Soriano (Belitung Raya Foundation, Indonesia, 2020)
Background: Breast cancer patients need to be treated not only physically and emotionally but also spiritually. Hence, the assessment of the spirituality of patients is essential to provide holistic nursing care. However, there was no culturally valid and reliable instrument that measures spirituality among Filipino women with breast cancer. Objective: The study was conducted to determine the psychometric properties of the spiritual index of well-being among Filipino women with breast cancer. Methods: A descriptive cross-sectional design was utilized in the study, and a sample of 170 Filipino women with breast cancer were included. The World Health Organization guidelines were used to translate the original instrument to Filipino, and content validity was computed using the Davis technique. Also, confirmatory factor analysis with maximum likelihood estimation was performed to assess the construct validity of the instrument. Cronbach’s α and item-total correlations were done to assess the internal consistency of the Filipino version of the spiritual index of well-being. Results: The Filipino version of the spiritual index of well-being had an item content validity index (I-CVI) ranging from 0.86 to 0.92 and a scale content validity index (S-CVI) of 0.95. The confirmatory factor analysis (CFA) showed factor loadings of 0.42 to 0.72. Also, the CFA model revealed a X2/df = 2.51, root mean square error of approximation= 0.074, comparative fit index= 0.091, goodness of fit index=0.98, Tucker-Lewis index= 0.93, incremental fit index= 0.91, and standard root mean square residual= 0.072. Conclusion: The Filipino version of the spiritual index of well-being was cross-culturally valid and reliable in measuring the spiritual index of well-being among Filipino women with breast cancer.